Observation of dielectric universalities in albumin, cytochrome C and Shewanella oneidensis MR-1 extracellular matrix - Motovilov, K A; Savinov, M; Zhukova, E S; Pronin, A A; Gagkaeva, Z V; Grinenko, V; Sidoruk, K V; Voeikova, T A; Barzilovich, P Yu; Grebenko, A K; Lisovskii, S V; Torgashev, V I; et al. (Scientific reports, 2017)
The electrodynamics of metals is well understood within the Drude conductivity model; properties of insulators and semiconductors are governed by a gap in the electronic states. But there is a great variety of disordered materials that do not fall in these categories and still respond to external field in an amazingly uniform manner. At radiofrequencies delocalized charges yield a frequency-independent conductivity σ 1(ν) whose magnitude exponentially decreases while cooling. With increasing frequency, dispersionless conductivity starts to reveal a power-law dependence σ 1(ν)∝ν s with s < 1 caused by hopping charge carriers. At low temperatures, such Universal Dielectric Response can cross over to another universal regime with nearly constant loss ε″∝σ1/ν = const. The powerful research potential based on such universalities is widely used in condensed matter physics. Here we study the broad-band (1-1012 Hz) dielectric response of Shewanella oneidensis MR-1 extracellular matrix, cytochrome C and serum albumin. Applying concepts of condensed matter physics, we identify transport mechanisms and a number of energy, time, frequency, spatial and temperature scales in these biological objects, which can provide us with deeper insight into the protein dynamics.
Keywords: Cattle; extracelulární matrix; elektrická vodivost; elektřina; albuminy; voda; Cytochromes c; Spectrum Analysis; Extracellular Matrix; Albumins; Water; Temperature; Electricity; Shewanella; cytochromy c; spektrální analýza; zvířata; Animals; Electric Conductivity; teplota; skot